Reading the landscape past -update: explaining the lack of on-farm tree planting in Ethiopia - Kassa, H.; Bekele, M.; Campbell, Bruce M. (2011)
Although tree planting initiatives by the state began by the end of the nineteenth century, on-farm tree planting has not been widespread, particularly on plots outside homesteads. Farmers particularly in central and northern Ethiopia are limited to growing trees mainly at homesteads indicating the need to identify the underlying discouraging factors. This paper examines the historical trend and current status of tree planting by smallholder farmers. In addition to reviewing historical and legal documents, the study solicited farmers' opinions and used maps and satellite images to examine past and recent features of a site in southern Ethiopia that represents the southern Rift Valley areas of the country and is characterised by low to medium tree cover. Major policy failures identified, and which persisted over a long period of time, include lack of tenure security, historical background that promoted free grazing, political and institutional instability, abrupt and radical changes in rural development policies and strategies and market distortions due to de facto open access of forest resources on the one hand and price control and lengthy permit requirements to sell wood and wood products produced on farms on the other. Unless these issues are addressed, the degrading landscapes will be worse off. The study clearly demonstrates that, in developing countries like Ethiopia, stable institutions, secure tenure and enabling policies are critical if tree planting is to be promoted for meeting farmers' own needs and growing market demands and thus increasing rural household income.